Seleksi dan Karakterisasi Bakteri Halotoleran Penghasil Enzim Amilase Dari Produk Fermentasi Ikan-Inasua: Selection and Characterization of Halotolerant Bacteria that produce Amylase Enzyme from Fish-Inasua Fermented Food - Karina Eku Dwinanda Gunawan; Jepri Agung Priyanto; Nisa Rachmania Mubarik (Departemen Biologi, Institut Pertanian Bogor, 2023)
Fish-inasua fermented food is a potential source to obtain halotolerant bacteria-producing amylase. Previously, four bacterial isolates such as IG12, IG6, IG66, and IG31, isolated from this food, have been reported to be able to produce protease and lipase enzyme, but their potential as amylase enzyme producers have not been studied. This study aims to characterize and test the potential of halotolerant bacteria isolated from this food in producing amylase enzymes. Based on Gram staining, four bacterial isolates were Gram-positive. The qualitative test of amylase on NA medium with the addition of 1% starch showed four bacteria were able to produce amylase in NaCl (0 to 5%)-containing medium. IG66 isolate was the most potential isolate because it had the highest enzyme activity in a medium with 5% NaCl concentration, which was 0.095 U/ml. The amylase activity was produced maximum at the 8th hour, which is the early stationary phase. Its maximum activity in the 5% NaCl-containing medium was at the 10th hour. In addition, amylase produced by IG66 isolate reached optimum activity at a temperature of 50°C and pH 7. This study concluded that IG66 isolate was the most potential halotolerant isolate that could be developed as an amylase-producing agent.